2020
DOI: 10.1073/pnas.1913810117
|View full text |Cite
|
Sign up to set email alerts
|

IGLV3-21 * 01 is an inherited risk factor for CLL through the acquisition of a single-point mutation enabling autonomous BCR signaling

Abstract: The prognosis of chronic lymphocytic leukemia (CLL) depends on different markers, including cytogenetic aberrations, oncogenic mutations, and mutational status of the immunoglobulin (Ig) heavy-chain variable (IGHV) gene. The number of IGHV mutations distinguishes mutated (M) CLL with a markedly superior prognosis from unmutated (UM) CLL cases. In addition, B cell antigen receptor (BCR) stereotypes as defined by IGHV usage and complementarity-determining regions (CDRs) classify ∼30% of CLL cases into prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(118 citation statements)
references
References 44 publications
8
97
2
Order By: Relevance
“…9 (G>C, glycine-arginine) of IGLV3-21*01 mediated by somatic hypermutation confers autonomous BCR signaling. 24 This change is present in 7-18% of CLL and seems responsible for the adverse outcome associated with the use of IGLV3-21 independently of the mutational status of the IGHV. 24,25 Epigenetic studies have shown that, although both CLL subtypes are antigen-experienced, M-CLL keeps a methylation signature of germinal center-experienced cells (memory-like B cells), whereas U-CLL has a pre-germinal center, naïve-like methylation signature .5,26 Of note, these epigenetic studies also identified a third subtype with an intermediate profile made of cases with moderate IGHV mutation levels.…”
Section: Cell Of Originmentioning
confidence: 99%
“…9 (G>C, glycine-arginine) of IGLV3-21*01 mediated by somatic hypermutation confers autonomous BCR signaling. 24 This change is present in 7-18% of CLL and seems responsible for the adverse outcome associated with the use of IGLV3-21 independently of the mutational status of the IGHV. 24,25 Epigenetic studies have shown that, although both CLL subtypes are antigen-experienced, M-CLL keeps a methylation signature of germinal center-experienced cells (memory-like B cells), whereas U-CLL has a pre-germinal center, naïve-like methylation signature .5,26 Of note, these epigenetic studies also identified a third subtype with an intermediate profile made of cases with moderate IGHV mutation levels.…”
Section: Cell Of Originmentioning
confidence: 99%
“…GerMaNet also helps the swift distribution of new reagents and data analysis tools among the centers. This approach has proven highly effective, as reflected by several joint publications within the GerMaNet .…”
Section: The German Mass Cytometry User Forum In Figuresmentioning
confidence: 99%
“…homotypic interaction between the LC and the CDR2 loop of another BCR ( [31]. A recently published article reported that the use of IGLV3-21 with this specific substitution (IGLV3-21 R110 in the authors' nomenclature) facilitates homotypic interaction in allele IGLV3-21*01 only [32]. The prevalence of this specific combination of mutation and allele is not confined to subset 2, but can be detected in up to »20% of CLL cases, despite being virtually absent in the BCR repertoire of healthy donors.…”
Section: Syntax: Synthesis Of the Bcrmentioning
confidence: 99%
“…The prevalence of this specific combination of mutation and allele is not confined to subset 2, but can be detected in up to »20% of CLL cases, despite being virtually absent in the BCR repertoire of healthy donors. Consequently, the authors define a subset "2L" based on the presence of IGLV3-21 R110 , which currently constitutes the largest CLL subset, and report the inferior prognosis of patients belonging to this subset in three independent cohorts [32].…”
Section: Syntax: Synthesis Of the Bcrmentioning
confidence: 99%